PENERAPAN MEDIA BERBASIS WEBSITE MENGGUNAKAN CANVA DALAM PEMBELAJARAN MENULIS PUISI PADA SISWA KELAS VI SEKOLAH DASAR DI KECAMATAN SUMEDANG UTARA - Amega Dewi; Asep Saepurokhman; E. Sulyati (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Learning to write poetry in elementary schools plays an important role in fostering creativity, empathy, and appreciation for literature. However, many students face difficulties due to limited imagination, word choice challenges, and low motivation. This study aims to determine the effectiveness of poetry writing instruction using a website-based medium with Canva in terms of process, outcomes, and students’ learning motivation among fourth-grade students in Sumedang Utara District. The research employed a quasi-experimental method with instruments including a teaching module, observation sheets, tests, and questionnaires, analyzed using both qualitative and quantitative approaches. The findings reveal that the learning process was carried out very effectively with an observation score of 91, student learning outcomes were classified as high with an average score of 71.0 and a z-score of -2.10 within the interval –2.33 < z < 2.33, and learning motivation was also high with an average score of 82.81. Keywords: Learning Media, Poetry, Website, Canva